Molecular and cellular effects of oncogene cooperation in a genetically accurate AML mouse model. - Reckzeh, K; Bereshchenko, O; Mead, A; Rehn, M; Kharazi, S; Jacobsen, SE; Nerlov, C; Cammenga, J (2012)
Biallelic CEBPA mutations and FMS-like tyrosine kinase receptor 3 (FLT3) length mutations are frequently identified in human acute myeloid leukemia (AML) with normal cytogenetics. However, the molecular and cellular mechanisms of oncogene cooperation remain unclear because of a lack of disease models. We have generated an AML mouse model using knockin mouse strains to study cooperation of an internal tandem duplication (ITD) mutation in the Flt3 gene with commonly observed CCAAT/enhancer binding protein alpha (C/EBPα) mutations. This study provides evidence that FLT3 ITD cooperates in leukemogenesis by enhancing the generation of leukemia-initiating granulocyte-monocyte progenitors (GMPs) otherwise prevented by a block in differentiation and skewed lineage priming induced by biallelic C/EBPα mutations. These cellular changes are accompanied by an upregulation of hematopoietic stem cell and STAT5 target genes. By gene expression analysis in premalignant populations, we further show a role of FLT3 ITD in activating genes involved in survival/transformation and chemoresistance. Both multipotent progenitors and GMP cells contain the potential to induce AML similar to corresponding cells in human AML samples showing that this model resembles human disease.